Phytotoxic Effects of Heavy Metals on Seed Germination and Seedling Growth of Medical Plant, Hyssop (Hyssopus officinalis L.) - Majid Sharifi-Rad (Journal of Medicinal Plants and By-products, 2017)
To assess the phytotoxicity of cadmium (Cd), chromium (Cr), copper (Cu), Nickel (Ni) and zinc (Zn) on seed germination and seedling growth of Hyssop (Hyssopus officinalis L.), experiments were performed in different aqueous concentrations (50, 100 and 150μM) of aforementioned heavy metals over the period of 14 sequential days. The results showed that heavy metals adversely affect the normal growth of plants by decreasing seed germination, reducing root and shoot length, and decreasing root and shoot weight. The toxicity effects of chosen heavy metals on seed germination can be organized by the grade order of inhibition as: Cr>Cd>Cu>Ni>Zn. The minimum root and shoot length were observed in Cd (150μM) and Cr (150μM) respectively. The minimum of fresh and dry root weight were recorded at Cd (150μM) and the minimum of fresh and dry shoot weight were observed at Cr (150 μM). These results illustrate a model system for different concentrations of heavy metals for their phytotoxicity effects and also for the seeds’ ability to negate the harmful effects of heavy metals in different types of irrigation waters and soils.